Air temperature data used by Mitton and Ferrenberg - Ferrenberg, Scott M. (Dryad Digital Repository, 2014)
Air temperature and growing degree day calculations for Mitton and Ferrenberg's reply to Bentz and Powell. This temperature data was pulled from raw data for 1953-present are available through the University of Colorado's Institute for Arctic and Alpine Research. The data presented are from the C-1 climate station located at the Niwot Ridge LTER site, 3018 m above sea level in Boulder County, Colorado, USA.